EFFECTIVENESS OF ANIBAZA MEDIA (DRUGS ANIMATION) ON KNOWLEDGE OF DRUG PREVENTION IN STREET ADOLESCENTS IN THE YAYASAN RUMAH IMPIAN YOGYAKARTA - Suryati Suryati (STIKES Pemkab Purworejo, 2023)
Background: Drugs are ingredients that when entering a person's body can cause damage to physical, psychic and mental health. UNODC, World Drug Report 2019 estimates that approximately 271 million people, or 5.5% of people aged 15 to 64 have used illegal drugs at least once (UNODC, 2021). Street teenagers are a very vulnerable group to be victims of drug abuse. Efforts that can be made to increase awareness and reduce the rate of drug abuse by providing information. Animation media is one of the most interesting and can increase motivation of adolescents. Method: this research is an experimental quantitative research using pre-experimental design (one group pre-post test design). The number of respondents was 20 adolescents used purposive sampling. The instrument uses ANIBAZA media, knowledge questionnaire and attitude questionnaire of drug prevention. Purpose: to determine the effectiveness of ANIBAZA (Narcotics Dangers Animation) on knowledge and attitudes of drug prevention in street teenagers at the Dream House. Results: Analysis of the study using the Wilcoxon test showed a significant difference between pre-test and post-test in adolescent knowledge with a p-value 0.000 and attitudes with a p-value 0.000. Conclusion: ANIBAZA media is effectively used as a health education to improve the knowledge and attitudes of street teenagers.